Perbedaan Tingkat Empati antar Mahasiswa Kepaniteraan Klinik Fakultas Kedokteran Universitas Lampung - christa selina; Merry Indah Sari; Oktafany (Medula, 2021)
Empathy is the ability to participate in feeling or imagining other people's feelings and this is one of the competencies that medical graduates must possess in order to create good doctor-patient relationships. A good doctor-patient relationships can improve their compliance and satisfaction with the services provided, so that it will provide better clinical results. However, it was found that during medical education, the level of student’s empathy could change due to various factors, one of them is level of study. The purpose of this study was to find out the mean empathy score between early and end clinical clerkship student, and to find out whether there were significant differences between the levels of study and the level of empathy of the clerkship students of the Medical Faculty of Lampung University. The research method used was an observational study with a cross sectional analytic approach at Abdoel Moeloek Hospital in February 2019. The research instrument used was The Jefferson's Scale of Physician Empathy - Student Version (JSPE - SV). Before processing the data, a normality test was carried out using the Kolmogorov Smirnov test. Then the data is processed using univariate tests and unpaired t-test as the bivariate tests. The results obtained are a mean empathy score of 100.09 which is included in the medium category. Based on the results of the unpaired t-test, it was found that there were statistically significant differences in the level of empathy among clerkship medical students in Medical Faculty of Lampung University.